Peran Tanaman Aromatik Dalam Menekan Perkembangan Hama Spodoptera litura Pada Tanaman Kubis - Johan A Patty (Agrologia, 2012)
Plant pests Spodoptera litura is one of the major insect pests that often lowers the cabbage yield. Various control techniques of this pest have been developed, such as the use of botanical pesticides. This study aimed to determine the role of aromatic plants in reducing S. litura population growth and plant damage intensity on cabbage. Experiments used intercropping combinations of cabbage-local basil (‘kemangi’), cabbage-tomato, cabbage-scallion and without aromatic plants as a control. The experimental was arranged in a Randomized Block Design. Parameters measured were larval population, damage intensity and fresh weight of cabbage crops. The results showed that all three cabbage intercropping with the aromatic plants were able to suppress population of S. litura and the resulted damage intensity of cabbage. The treatment of cabbage intercropping with local basil could reduce larval populations of S. litura (to 0.84 larvae) or only 8 larvae per 10 plants and with the lowest crop damage intensity (3.32%) and highest crop weight (486.6 g) per plant.